2008
DOI: 10.2147/copd.s948
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of post-bronchodilator pulmonary function testing to distinguish between stable, moderate to severe COPD and asthma

Abstract: Objective: The GOLD guidelines suggest that the presence of a post-bronchodilator forced expiratory volume in one second (FEV 1 ) Ͻ 80% of the predicted value in combination with a FEV 1 /forced vital capacity (FVC) Ͻ 70% confi rms the diagnosis of COPD. Limited data exist regarding the accuracy of these criteria to distinguish between COPD and asthma. The aim of this study therefore was to investigate the diagnostic value of post-bronchodilator lung function parameters in obstructive lung disease. Methods:The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“… 7 10 In addition to this diagnostic dilemma, there is lack of knowledge about the importance of pre-respectively post-bronchodilation airflow limitation in relation to the clinical picture and prognosis of obstructive airway diseases. 11 Also, the presence of comorbid conditions is important when evaluating clinical characteristics in relation to prognosis. 12 15 Comorbidities are common in COPD, and it has been estimated that 68% of subjects with COPD have cardiovascular disease, diabetes, or depression.…”
Section: Introductionmentioning
confidence: 99%
“… 7 10 In addition to this diagnostic dilemma, there is lack of knowledge about the importance of pre-respectively post-bronchodilation airflow limitation in relation to the clinical picture and prognosis of obstructive airway diseases. 11 Also, the presence of comorbid conditions is important when evaluating clinical characteristics in relation to prognosis. 12 15 Comorbidities are common in COPD, and it has been estimated that 68% of subjects with COPD have cardiovascular disease, diabetes, or depression.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these constraints, up to 60% of COPD subjects may show spirometric reversibility as defined by the American Thoracic Society. 4,5 The Global Initiative for Obstructive Lung Disease (GOLD) and South African guidelines consider the definition for COPD exemplified by the post-bronchodilator forced expiratory volume in one second (FEV 1 )/forced vital capacity (FVC) of < 0.70 as being diagnostic. 1,2 Another limitation, however, is that the criterion is neither sensitive nor definitive for the detection of COPD.…”
Section: Limitations Of Spirometry In Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…1,2 Another limitation, however, is that the criterion is neither sensitive nor definitive for the detection of COPD. 4 The SPIROMICS (Subpopulations and Intermediate Outcome Measures in COPD Study) research group reported on an observational study involving 2736 current or former smokers. 6 Respiratory symptoms were present in 50% of subjects with spirometry in the normal range (who would not have met the COPD definition).…”
Section: Limitations Of Spirometry In Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…Asthma and chronic obstructive pulmonary disease (COPD) are complex chronic diseases with a high prevalence across the globe. Asthma is an inflammatory disease characterised by airway hyperresponsiveness that is mostly reversible, while COPD is an irreversible, progressive airway obstruction [ 1 ]. A diagnosis of obstructive pulmonary disease usually depends on symptomatic features.…”
Section: Introductionmentioning
confidence: 99%